Field evaluation of oil formulations of the fungus Beauveria bassiana (Bals.) Vuill - VÉLEZ-ARANGO, PATRICIA EUGENIA (Revista Colombiana de Entomología, 1996)
In an attempt to evaluate the viability of the fungus Beauveria bassiana (Bb-9205) on the coffee ecosystem, under sunlight and artificial shadow (Naranjal Central Station, Cenicafé, 1,400 masl), spraying of the fungus Bb in water (10 ml of oil for agricultural) use, in 20 1 of water) and Bb in Tersol oil (10% of oil formulation of the fungus in water, plus the emulsifier agent: 500 m1/1001 of formulation) was carried out. The sun and shadow plots (12 for each condition) were randomly selected, six for the water preparation, and six for the oil formulation of the fungus. Plots of 50 trees with the borders were selected, for a total number of 30 branches and 120 coffee berries per branch (experimental unit). The sprayings were made with a low volume "Ulvafan" sprayer, with a nozzle with a flux of 70 c/min. The spraying volume per branch was 17.5 ml, with a dose of 4.02 x 109 conidia/ branch. The spraying was directed to the upper and lower side of the branches. The viability of the fungus Bb, on the selected berries, was evaluated at different times (0, 2, 4, 5, 24, 48, and 336 hours) of exposure of the preparations to the luminosity factors. The estimation was made by the method of culture of successive dilutions of the initial sample (120 berries in 30 ml of 10% glycerol) on the surface of a selective medium for the isolate of B. bassiana. The treatments were evaluated under simple classification design with a factorial arrange 2x2 (two luminosity conditions, sun and artificial shadow, and two preparations on the fungus, oil, and water). In order to measure the response of the treatments, the variable relative ratio of reduction 01 the viability of the fungus Bb-9205 in each treatment was evaluated, and the selected treatment was that with the lower relative ratio, which had the lower reduction of the viability throughout time. The analysis of the results did not show any difference between treatments under sun and shadow, neither the interaction preparation-luminosity condition. The mean value of the relative ratio of reduction of the viability of the treatments was 45.97%. Recovery of the fungus B. bassiana in the evaluated times was registered for all treatments. The response shows the persistence of both preparations of the fungus B. bassiana (oil and water) on the coffee ecosystem, under sun and shadow conditions, throughout the time of evaluation and its biological potenti al to control the coffee berry borer Hypothenemus hampei.